2020
DOI: 10.1148/radiol.2020192227
|View full text |Cite
|
Sign up to set email alerts
|

Adrenal Adenomas versus Metastases: Diagnostic Performance of Dual-Energy Spectral CT Virtual Noncontrast Imaging and Iodine Maps

Abstract: GASTROINTESTINAL IMAGINGG iven the extensive use of medical cross-sectional imaging, the incidental detection of adrenal lesions has concomitantly increased, occurring in approximately 5%-8% of patients undergoing CT (1-5). Although most incidental adrenal lesions are benign adenomas, the most common clinical dilemma has been the differentiation between adenomas and metastases, particularly among patients with a history of extra-adrenal malignancy (1-3). Because the presence of metastasis can affect treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
41
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 74 publications
(55 citation statements)
references
References 37 publications
(78 reference statements)
8
41
0
3
Order By: Relevance
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]). We introduced a new imaging parameter of relative enhancement ratio by combining unenhanced attenuation and absolute enhancement, yielding a diagnostic performance almost comparable with the previously reported washout CT (sensitivity, 86% vs 82%-92%; specificity, 95% vs 87%-100%) for the discrimination of lipid-poor adenomas (5,9,10,21).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…In our study, lipid-poor adenomas showed a lower unenhanced attenuation than nonadenomas (22 HU 6 6 vs 34 HU 6 7; P , .001), as in previous studies (5,(9)(10)(11)(12)(19)(20)(21)(22). Additionally, the absolute enhancement of adenomas was 1.5-fold higher than nonadenomas (P , .001), which is also corroborated by data from numerous studies wherein adenomas had higher (up to 2.2-fold) absolute enhancement compared with nonadenomas, mostly comprising metastases (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)14,16,22,29,30) (Table E4 [online]). We introduced a new imaging parameter of relative enhancement ratio by combining unenhanced attenuation and absolute enhancement, yielding a diagnostic performance almost comparable with the previously reported washout CT (sensitivity, 86% vs 82%-92%; specificity, 95% vs 87%-100%) for the discrimination of lipid-poor adenomas (5,9,10,21).…”
Section: Discussionsupporting
confidence: 84%
“…In this study, adrenal metastases from hepatocellular carcinoma (HCC), renal cell carcinoma (RCC), pheochromocytomas, and adrenocortical carcinomas were categorized as hypervascular nonadenomas, which reportedly mimic adenomas at contrast-enhancement CT (19,(23)(24)(25)(26)(27)(28). In a prior study (29) on contrast-enhanced dual-energy CT that evaluated the diagnostic performance of virtual noncontrast attenuation and iodine density for differentiating adrenal adenomas from metastases, we reported on 36 patients included in the current study. All CT images were acquired at different times and with use of different scanners than those in the prior study.…”
Section: Reference Standardmentioning
confidence: 99%
See 2 more Smart Citations
“…However, no studies have reported the usefulness of rest cardiac DECT for ACS. Recently, dual-layer DECT (DL-DECT) has been introduced for clinical use [11][12][13]. DL-DECT can overcome the disadvantage of increased image noise at low-energy levels.…”
Section: Introductionmentioning
confidence: 99%